(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Despite the prevalence of chocolate-based inclusions, the impact of polyglycerol polyricinoleate (PGPR) on chocolate glaze properties is limited. The objectives of this study are to determine the effects of cocoa butter (CB) concentrations and lecithin to PGPR (L:PGPR) blend ratios on the rheological properties of chocolate glaze and to identify the impact of the thickness and stability of the selected chocolate glaze by different storage conditions. Rheological analysis, volume take-up, surface area and density were measured to calculate the glaze thickness for three consecutive layers. Chocolate glaze is made of either 35% or 40% CB, with 0.7% emulsifier of three different L:PGPR ratios (10:0, 7:3, and 3:7). Sample D (35% CB, 0.49% L, 0.21% PGPR) showed similar (p > 0.05) Casson yield stress (1.230 ± 0.297 Pa) and Casson viscosity (0.910 ± 0.127 Pa s) as control (1.578 ± 0.195 Pa, 0.769 ± 0.010 Pa s) made of 40% CB with 0.7% lecithin. Water activity and total plate count were within satisfactory limits. Rheological behaviours and shelf stability for both samples were similar (p < 0.05) up until 14 days of storage. This study may serve as a reference for industry to use PGPR to replace CB and lecithin in chocolate glaze applications of bakery products.